Physical Activity, Cardiorespiratory Fitness and Body Mass Index as Predictors of Substantial Weight Gain and Obesity: The Canadian Physical Activity Longitudinal Study - Brien, Susan E. (Can J Public Health, 2007)
BACKGROUND: Obesity is a growing health issue in Canada and the identification of the determinants of obesity is important for the development of prevention strategies. The purpose of this investigation was to determine the relationships between physical activity, cardiorespiratory fitness, body mass index (BMI), and the development of future obesity. METHODS: The sample included 459 adults (18+ y; 223 men, 236 women) from the Canadian Physical Activity Longitudinal Study (PALS; 2002–04). Data on physical activity, smoking, alcohol consumption, BMI, and cardiorespiratory fitness (VO(2)(m)(a)(x)) were collected in 1981 and 1988. The mean BMI, physical activity, and VO(2max) were calculated across the 1981 and 1988 measures. Self-reported height and weight were collected in the 2002–04 survey, and participants were classified as overweight (BMI 25 to 29.9 kg/m2) or obese (BMI ≥30 kg/m2). Logistic regression was used to predict overweight, obesity or substantial weight gain (10 kg or more) in 2002–04, controlling for age, sex, smoking and alcohol use. RESULTS: Higher VO(2max) in 1981–88 was associated with lower odds of obesity in 2002–04 (OR=0.87; 95% CI: 0.76–0.99, p<0.05), and higher BMI in 1981–88 was associated with higher odds of obesity in 2002–04 (1.84; 1.52–2.20, p<0.0001). In women, higher VO(2max)(0.82; 0.72–0.93) resulted in lower odds of a 10 kg weight gain. CONCLUSIONS: The results indicate that cardiorespiratory fitness and previous BMI are important predictors of future weight gain and obesity, and should be incorporated in strategies to identify individuals at increased risk of obesity.